Peran Digitalisasi Arsip untuk Meningkatkan Efektivitas Manajemen Dokumen Arsip di Dinas Arsip Kota Semarang - Janah, Eliya Uslifatul; Hidayah, Putri Fitria; Adysti, Rachmania Naura; Arjuna, Romeo Herdha (TSAQOFAH, 2025)
With the development of information technology, records management has become a very important part of organizational management, both in the public and private sectors. The purpose of this study is to see how the implementation of archive digitization in Semarang City Archives can improve the efficiency of document management. This research also investigates the problems faced by the Semarang City Archives and Library Department and how it impacts public services. Data was collected through interviews and direct observation using a descriptive qualitative approach. A thorough analysis was conducted to determine the role of digitization in improving the efficiency and effectiveness of records management. The results showed that, compared to manual methods, archive digitization can improve document accessibility, efficiency, and security. However, digitization has some barriers, such as limited infrastructure, technological devices, and human resources. The process that has been carried out includes the creation of an application system, the implementation of digital archive authentication, and the reorganization of the archive space, as well as with plans to create more efficient applications. With digitization, it is expected that transparency, accountability, and ease of access to archives for the public and educational institutions will increase. To ensure sustainability and improvement of public services, periodic evaluation of the digitization program with clear performance indicators is needed. These results can provide strategic recommendations for better development of future archive digitization systems.